Annika. Season one [videorecording (DVD)] - Walker, Nick (Screenwriter) (PBS Distribution, 2022)
DI Annika Strandhed, the speedboat-driving head of Glasgow's newly-formed Marine Homicide Unit, juggles baffling cases and a rebellious teenage daughter. Joined by DS Michael McAndrews, Annika's old colleague; DC Blair Ferguson, the forensic brains behind the unit; and DS Tyrone Clarke, the new cop at the station.